All about Sergio Leone [the ultimate compendium] - De Fornari, Oreste 1951- (Gremese International, 2019)
The ultimate compendium of the films, life, scripts, quotes, reviews and photos of one of the greatest directors in world cinema. --Cover
Keywords: Leone, Sergio -- 1929-1989; Leone, Sergio / 1929-1989; Motion picture producers and directors / Biography; Producteurs et réalisateurs de cinéma / Biographies; Leone, Sergio / 1929-1989 / https://id.oclc.org/worldcat/entity/E39PBJpyqKhDdTCFQ9yMjR3CwC; Motion picture producers and directors; Biography; Biographies